CONTENT AND STRUCTURE OF THE COURSE “INFORMATION AND COMMUNICATION TECHNOLOGIES IN PEDAGOGICAL STUDIES” - Liudmyla H. Havrilova H. Havrilova; Yana V. Topolnik; Liudmyla O. Kuhar; Liudmyla A. Matviychuk (Інформаційні технології і засоби навчання, 2018)
The article describes the content and structure of the discipline “Information and Communication Technologies in Pedagogical Studies”, which was introduced into the curriculum of training future Doctors of Philosophy in the field of knowledge “Education”. The course consists of two modules: 1) theoretical basis of using information and communication technologies in pedagogical studies; 2) using information and communication technologies at different stages of pedagogical study. In addition, the topics of lectures, general content of practical classes and independent work are given. The content of practical classes contains work in cloud services, checking scientific materials for plagiarism, organizing and conducting questionnaires and testing, creating websites, blogs, etc. Among the tasks of independent work: the creation of a distant course in Moodle, work in MS Excel, the statistical recording of the pedagogical experiment data, the creation of presentations (MS Power Point, Prezi). The results of the implementation of the course in the training of future Doctors of Philosophy in the field of education were monitored; the levels of formation of their ICT competence were. The authors used survey methods, testing, creative tasks, etc. In particular, they described the testing procedure, which was conducted in compliance with all the necessary requirements for designing tests, which ensured the reliability and validity of the monitoring. The authors proved the urgency of implementing the mentioned course into the future scholars’ training, which corresponds to the modern tendencies of education informatization. The course “ICT in Pedagogical Studies” reveals a complex of opportunities and prospects of using computer technologies during scientific and pedagogical research, provides quality training of the specialists with a new type of thinking, promotes the efficiency of their research and pedagogical activity, which is confirmed by the results of implementing the course into the training of the future Doctors of Philosophy in the field of knowledge “Education”.